Language and Education - Fillmore, Lily Wong. ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1986)
The relationship between language and education is considered, focusing on the central role of language in learning, and two kinds of research concerned with language and educational issues are discussed. Linguistic research focuses on the language aspects and treats the educational aspect as the contextual surrounding of the problem. Educational research focuses on the learning aspect of the problem and sees language as a variable that could explain the outcome. Differences between linguists and educational researchers' domains of interest reflect important differences in their initial assumptions and in how they interpret the evidence. A review of research in dialect variation, specifically Black English Vernacular, and its effect on academic achievement is reported from both a linguistic and educational approach. The application of linguistic issues to educational problems such as literacy, the effects of dialects on learning, how well teachers use the language, and how well students understand the language of instruction is highlighted, and research on language teaching, language proficiency and schooling, language proficiency assessment, and training is discussed. It is concluded that both educators and linguists can learn much from each other. (DJD)
ERIC Note: In: Proceedings of the Annual Eastern States Conference on Linguistics (3rd, Pittsburgh, PA, October 10-11, The complete Proceedings are available from the Dept. of Linguistics, Ohio State University, Columbus.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Academic Achievement; Black Dialects; Comparative Analysis; Dialect Studies; Educational Objectives; Educational Research; Educational Researchers; English (Second Language); Language of Instruction; Language Proficiency; Language Research; Language Skills; Literacy; Measures (Individuals); Research Methodology; Second Language Instruction; Linguists; Information Analyses; Speeches/Meeting Papers; Opinion Papers